Pengaruh Prinsip Kaizen, Efisiensi, dan Disiplin Kerja terhadap Kinerja Karyawan - Ihza Muhammad Erlandy; Benny Gunawan; Rojuaniah Rojuaniah; Puspita Chairun Nisa (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the influence of kaizen principles, efficiency, and work discipline on employee performance. The research method used is a quantitative approach with regression analysis techniques to measure the relationship between these variables. The results of the study indicate that the principles of kaizen, efficiency, and work discipline have a positive and significant influence on employee performance, both partially and simultaneously. The application of these three variables consistently can increase productivity, efficiency, and work quality, while creating an innovative and adaptive work culture. Thus, the implementation of the principles of kaizen, efficiency, and work discipline can be an effective strategy in improving employee performance and supporting the company's competitiveness in the era of globalization.